Republic of the Marshall Islands : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of the Marshall Islands. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlight that growth in the Marshallese economy is estimated to have accelerated to about 3.5 percent in FY2017 (ending September 30) with a strong pick-up in fisheries and construction, with the latter owing to the resumption of infrastructure projects. Consumer prices started to rise again in mid-2017, with annual consumer price index inflation at 1.1 percent in 2017Q4. Growth is expected to remain robust at about 2.5 percent in FY2018 and about 1.5 percent over the medium term, underpinned by further increases in infrastructure spending. Inflation is expected to rise gradually to about 2 percent over the medium term.